Lewis Acid Catalyzed [4+1] Cycloaddition of o-Quinone Methides and Isocyanides: Mild and Efficient Synthesis of 3-Aryl-2-aminobenzofurans - Yang, Cun; Li, Yanze; Huang, Qiwen; Li, Xinyao (Synlett, 2023)
We herein report a mild and efficient synthesis of 3-aryl-2-aminobenzofurans by Lewis acid catalyzed [4+1] cycloaddition of in situ generated o-quinone methides and isocyanides. Compared with the well-known methods, the current reactions are carried out under mild conditions and feature wide substrate scope in high yields at ambient temperature at catalyst loadings as low as 1 mol%. DFT calculations show dehydration as the rate-determining step, a stepwise [4+1] cycloaddition process, and the Lewis acid as dual roles in accelerating dehydration and cycloaddition reaction.
Keywords: Lewis acid; [4+1] cycloaddition; o-quinone methides; isocyanides; benzofurans